A new test study on measurement of bias aircraft tire blowout. (April 2017) - Wang, Yaohua; Liu, Guofeng; Wu, Zhibin
Failure of aircraft tires is a common cause for aviation accidents, whose results range from abnormal taking-off and landing process to fatal air crashes. Those consequences should not be neglected; hence, an authentication of airworthiness is necessary for the development of new aircrafts. Failure of aircraft tires can be caused by numerous factors and can be categorized into various modes. The related tests are of great significance for newly developed aircrafts to pass the authentication system. However, failures of aircraft tires can be unexpected, drastic, and extremely dangerous, which adds to the difficulties in tests. Besides, the test methods used currently contain insurmountable defects. In this article, a new test apparatus is developed to research the blowout of bias aircraft tires, which is in accordance with the Joint Aviation Authorities standard, and a test scheme is designed. With the jet flow field formed by the test apparatus and the comparison between simulation results and test data, the reliability of the test apparatus is proved. Ergo, a new test method for the airworthiness authentication of tire failures has been developed.